The Effect Of Using Fluentu on Student' Reading Comprehension at Grade Eleven - Manurung, Sri Maneni; Purba, Rudiarman; Marpaung, Tiarma Intan; Siahaan, Mungkap Mangapul (CV Putra Publisher, 2026)
This research aims to investigate the effect of the FluentU application on the reading comprehension of eleventh-grade students. FluentU is an AI-assisted language learning application that uses authentic video content, such as movie clips, music videos, and interviews, integrated with interactive subtitles and vocabulary tools to improve learners’ listening, reading, and comprehension skills in a real-world context. This study employed a quantitative research design with a quasi-experimental approach. The population of this research consisted of eleventh-grade students of SMK Negeri 1 Siantar in the academic year 2024/2025. Two classes were taken as the sample: XIBS-1 as the experimental group (36 students) and XIBS-2 as the control group (36 students). The samples were selected using purposive sampling. The experimental group was taught using the FluentU application, while the control group was taught using conventional methods. Data were collected through pre-tests and post-tests administered to both groups. The findings showed that the mean pre-test score of the experimental group was 67.78, while the control group obtained 62.78. Furthermore, the mean post-test score of the experimental group was 81.94, compared to 75.14 in the control group. The standard deviations were 8.475 for the experimental group and 7.791 for the control group. Data analysis using the t-test revealed a Sig. (2-tailed) value of 0.000 < 0.05, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Therefore, it can be concluded that the use of the FluentU application has a significant effect on the reading comprehension of eleventh-grade students at SMK Negeri 1 Siantar